Attitude of Secondary School Teachers Towards the Teaching of Sex Education in Osogbo Local Government Area of Osun State (Faculty of Social Science, Universitas Negeri Semarang, 2021)
The study was on the attitudes of secondary school teachers towards the teaching ofÂ sex education in Osogbo, the target population comprises all the secondary schools in Osogbo Local Government Area of Osun state. Ten secondary schools were randomly sampled and 20 teachers were randomly selected from each school sampled as respondents. A questionnaire entitled â€œAttitude of Secondary School Teachers Towards the Teaching of Sex Education (ASSTTTSE)â€, with psychometric properties of content validity and 0.81 reliability index. percentage-test and Analysis of Variance (ANOVA) statistical method were used in analyzing the data collected at 0.05 level of significance. The findings showed that there was no significant difference in respondentsâ€™ views about the attitudes of secondary school teachers towards sex education based on gender and school type, except on the bases of age. It was recommended among others that; teachers should teach certain aspects of sexuality at schools that the students will be familiar with societal expectations of their future roles as husband and wife.